Agreement between admission and discharge diagnoses: analysis by the groups of International Classification of Diseases, 10th revision - Mihailović, Nataša M; Trajković, Goran; Simić-Vukomanović, Ivana; Ristić, Svetlana; Kocić, Sanja (Vojnosanitetski pregled, 2017)
Background/Aim. Admission diagnosis represents the diagnosis of an illness, injury or condition due to which a patient is referred to hospital to be admitted. Discharge diagnosis represents the main reason of illness or condition due to which a patient is admitted. The aim of this study was to analyze the agreement between admission diagnostic groups and discharge diagnostic groups of patients in the Clinical Center Kragujevac in the period from January 1, 2006 to December 31, 2013 on the basis of the hospitalization report. Methods. From the basic set of reports, 5% of random samples were singled out and they contained 20,422 reports. Out of the given number of reports, 18,173 hospitalization reports were complete and then further analyzed in the paper. Admission diagnostic groups given by the primary care doctor were compared with discharge diagnostic groups filled out by the practicing physician in the hospital ward from which a patient was discharged. The agreement of these two diagnostic groups was an indication of the high-quality performance of the primary care doctor. Agreement analysis was conducted using Cohen’s Kappa statistics. Results. Agreement analysis showed that the values of the Kappa coefficient for the five leading admission diagnostic groups were in the range of κ = 0.61 to κ = 0.94. The values of the Kappa coefficient for the five most common discharge diagnostic groups were in the range of κ = 0.55 to κ = 0.81. Conclusion. Hospitalization report is a reliable individual report on inpatient care, so it could be used in determining the degree of agreement between admission diagnostic groups and discharge diagnostic groups.
Keywords: patient admission; patient discharge; diagnosis; international classification of diseases